1984
DOI: 10.1080/07315724.1984.10720054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nutritional support service on VA surgical patients.

Abstract: The impact of a multidisciplinary Nutritional Support Service (NSS) on the reduction of complication was evaluated in 78 consecutive patients who received total parenteral nutrition (TPN) on the same VA surgical service. Patients were placed into one of three groups (pre-NSS, transition-NSS, post-NSS) based on the evolution of the NSS. A significant reduction in catheter sepsis was observed and was attributable to the establishment of an NSS, specifically, a nurse specialist and protocols for catheter insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 4 publications
1
42
0
1
Order By: Relevance
“…There were no randomized controlled trials identified, and all 11 studies were comparative in design, 4 with concurrent controls 2-4,12 and 7 with historical controls. 5,6,[13][14][15][16][17] The methodological quality of the studies were limited, as none of the studies provided a clear description of the inclusion and exclusion criteria, and only 2 studies 4,13 reported that the groups were treated identically other than for the named intervention. Table I presents a summary of the methodological quality of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no randomized controlled trials identified, and all 11 studies were comparative in design, 4 with concurrent controls 2-4,12 and 7 with historical controls. 5,6,[13][14][15][16][17] The methodological quality of the studies were limited, as none of the studies provided a clear description of the inclusion and exclusion criteria, and only 2 studies 4,13 reported that the groups were treated identically other than for the named intervention. Table I presents a summary of the methodological quality of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes in the trials were generally small and ranged from 28 2 to 285, 17 subjects, with 5 studies having unequal sample sizes between the comparison groups. 3,5,6,15,17 The mean duration for the administration of TPN therapy ranged from 7.1 days 2 to 26 days 16 and was administered using either a central [3][4][5][6][12][13][14][15]17 or peripheral 4,5,12 venous catheter. In 2 studies, 2,4 patients received oral and or enteral nutrition during the transitional phase of TPN therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous papers have associated the establishment of an NST with improved clinical outcome and/or reduction in costS.25, 28,30,34,66,[70][71][72][73][74][75][76][77][78][79][80][81][82][83] The apparent implication of such data is that every hospital should have an NST. A difficulty with interpreting and implementing such a conclusion is the wide variability in already established NSTs, as discussed above.…”
Section: Data On the Efffects Of The Nstmentioning
confidence: 99%